PENGARUH E-WEBSITE QUALITY DAN E-SERVICE QUALITY TERHADAP E-REPURCHASE INTENTION MELALUI E-WORD OF MOUTH (E-WOM) SEBAGAI VARIABEL INTERVENING - Noor Septi Lestari; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2020)
This study aims to explain the effect of website quality and e-service quality on e-repurchase intention through e-word of mouth as an intervening variable. The sample in this study was 100 Muslim women who had bought Hijab Alila products at least 2 times online.The results of this study indicate that the variable website quality and e-service quality affect e-word of mouth. Variable e-website quality and e-service quality affect e-repurchase intention. The e-word of mouth variable influences e-repurchase intention. While e-website quality, e-service quality, and e-word of mouth variables simultaneously have no significant effect on e-repurchase intention. So researchers provide advice on Hijab Alila in order to set a schedule for the latest product information on a regular basis so that the latest products can be seen one-on-one by customers and provide training to employees on how to resolve customer complaints.